Experiences of midwives in implementing the fifth stage of function in the integrated service posts to prevent anemia in pregnant women during the COVID-19 pandemic in Indonesia - Mien, Mien; Ananda, Siti Hadrayanti; Indriastuti, Diah; Tahiruddin, Tahiruddin (YCAB Publisher & IAKMI SULTRA, 2021)
Background: Anemia is an indirect cause of death for pregnant women and women in labor due to bleeding. One of the inabilities of the uterine muscles to contract is caused by anemia. The use of integrated service posts or Posyandu, especially in the fourth and fifth steps as a stage of individual health promotion, should prevent anemia in mothers.Objective: The purpose of this study was to explore the experiences of midwives in the implementation of the fifth stage of function in integrated service posts in relation to preventing anemia in mothers.Methods: This was a qualitative study with a phenomenological approach conducted from January to November 2020. The participants consisted of eight midwives, two nutritionists, one laboratory analyst, six cadres, and two pregnant women. The participants were selected using accidental sampling in the Poasia Public Health Center working area, Kendari, Southeast Sulawesi of Indonesia.Results: The results showed two themes related to the implementation of the fifth stage of the integrated service post activities: pregnancy examination and treatment of anemia.Conclusion: The implementation of the fifth stage in the integrated service postal service has been carried out maximally utilizing the resources owned by the public health center and the community. However, midwives receive additional burdens for its implementation because cadres are less able to provide health education for pregnant women, especially regarding anemia. The study was supported by the Research and Community Engagement Directory (DRPM) of the Republic of Indonesia.